Vocal Repertoire, Social Structure and Feeding Preferences of Australian and Antarctic Killer Whales (Orcinus orca) - Wellard, Rebecca (Curtin University, 2018)
This thesis aimed to improve the understanding of killer whale populations in the Australian and Antarctic regions. Visual surveys, photo-identification and passive acoustic recordings were combined to study these populations. This study describes the call repertoire of killer whales found in Australian and Antarctic waters, presents an acoustic comparison between sympatric ecotypes in Antarctic waters and investigates the sociality and feeding preferences of killer whales in the Bremer Sub-Basin.